"Trust Is Good, Control Is Better": Multiparty Government and Legislative Organization. (March 2016) - André, Audrey; Depauw, Sam; Martin, Shane
Even though institutional design clearly shapes legislative processes and outputs, explanation of cross-national variation in how legislatures are organized remains elusive. Building on research that emphasizes the role of legislatures in enforcing coalition agreements, we provide new data on committee structures in thirty-one parliamentary democracies, demonstrating that where multiparty government is the norm, legislatures tend to develop strong committees that are structurally equipped to enable the governing parties to keep tabs on one another's ministers. To probe the institutional argument further, we present a case study of committee reform in the Irish parliament. We demonstrate that institutional change within the Irish parliament is directly related to the shift from single-party to multiparty government and in particular to the desire of the smaller coalition party to be able to keep tabs on the larger party's ministers. The paper aims to spark a deeper dialogue among party and legislative scholars in search of the micro-foundations of legislative organization.